Framework for Assessing Financial Literacy and Superannuation Investment Choice Decisions - Natalie Gallery; Cameron Newton; Chrisann Palm (Australasian Accounting, Business and Finance Journal, 2011)
There is a worldwide trend towards rapidly growing defined contribution pension funds in terms of assets and membership, and the choices available to individuals. This has shifted the decisionmaking responsibility to fund members for managing the investment of their retirement savings. This change has given rise to a phenomenon where most superannuation fund members are responsible for either actively choosing or passively relying on their funds’ default investment options. Prior research identifies that deficiencies in financial literacy is one of the causes of inertia in financial decision-making and findings from international and Australian studies show that financial illiteracy is wide-spread. Given the potential significant economic and social consequences of poor financial decision-making in superannuation matters, this paper proposes a framework by which the various demographic, social and contextual factors that influence fund members’ financial literacy and its association with investment choice decisions are explored. Enhanced theoretical and empirical understanding of the factors that are associated with active/passive investment choice decisions would enable development of well-targeted financial education programs.
Keywords: Financial literacy; Investment choice; Superannuation; Australia